Efforts of PAI Teachers in Shaping the Character of Discipline and Responsibility of Students at MA Darul Ma'arif Payaman Lamongan - Nafisah, Hilyatun; Nashihin, Muhammad (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2024)
Character cultivation has an important role in overcoming the problems that occur in the world of education today. It is often found in various schools that students arrive late to school. Apart from that, there are also disciplinary problems that need to be addressed. This research aims to determine the role of Islamic religious education subject teachers in forming students' character values of discipline and responsibility at MA Darul Ma'arif Payaman Solokuro Lamongan, as well as to find out what supporting and inhibiting factors are in forming students' character values of discipline and responsibility. at MA Darul Ma'arif Payaman Solokuro Lamongan. This type of research is qualitative research or descriptive research. Descriptive type using field study methods (field research). The main research informants were Islamic religious education teachers and students of MA Darul Ma'arif Payaman Solokuro Lamongan, while secondary data sources were obtained in the form of documentation that had been determined by the researcher. Data collection techniques used participatory observation, free guided interviews and documentation. Based on the analysis carried out by researchers, it can be concluded that the formation of an attitude of discipline and responsibility is carried out using several mechanisms or methods, such as (a) habituation (b) providing examples or role models (c) awareness or motivation (d) control and supervision and ( e) the existence of regulations and punishments. There are also supporting factors such as (a) commitment of teachers and staff, (b) implementation of school programs, (c) implementation of local content. Meanwhile, the inhibiting factors are (a) lack of student awareness, (b) low student interest in learning.